Metacognitive feelings, conflict detection and illusion of linearity - Putarek, Vanja; Vlahović-Štetić, Vesna (2019)
Studies on conflict detection have suggested that people are sensitive to conflict between their heuristic judgment and logical or probabilistic principles, but due to the inhibition failure, they do not disregard appealing heuristic answer. However, these studies were mostly conducted on syllogistic reasoning and base-rate problems. The question is whether findings about conflict detection can be applied to other materials and areas of reasoning. Current study focused on the illusion of linearity, in which people over-rely on linearity heuristic. Therefore, the aim of this study was to examine whether students detect the conflict between heuristic answer and logical/mathematical principles. Participants were 113 secondary school students from Zagreb, Croatia. Data were collected using a computer program, which consisted of instructions, 20 problems (10 linear and 10 non-linear) and sociodemographic questions. Problems were presented randomly in multiple-choice format and had three offered answers (correct answer, distractor, "none of the answers"). Response time for each problem was also measured. Results demonstrated that students mostly solved non-linear problems incorrectly and in accordance with linearity heuristic. Furthermore, the analysis of metacognitive feelings of confidence and difficulty revealed that students detected conflict between heuristic answer and mathematical principles. Moreover, overriding heuristic answer and generating correct answer to non-linear problems resulted in increased response time. Comparison between metacognitive feelings and response time in linear and non-linear problems indicates the importance of processing fluency and inhibition failure in the occurrence of the illusion of linearity.
Bibliografija: str. 188-192.
Abstract.
Keywords: Metakognitivni osjećaji -- Otkrivanje sukoba -- Iluzija linearnosti